2023
DOI: 10.1021/acsnano.3c01094
|View full text |Cite
|
Sign up to set email alerts
|

Development of Multifunctional Nanoencapsulated trans-Resveratrol/Chitosan Nutraceutical Edible Coating for Strawberry Preservation

Abstract: Phytochemical nanoencapsulation for nutrient delivery and edible coatings for perishable food preservation are two emerging technologies. Leveraging the strong antimicrobial function of phytochemical nutrients, we propose convergent research to integrate the two technologies by embedding phytochemical-encapsulated nanoparticles in an edible coating on fresh fruits to achieve multiple functions. In particular, we report the study of an edible coating on strawberries that is composited of trans-resveratrol (R)-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…After being coated by dipping and stored at a temperature of 19–25 °C and humidity of 40–50% for 7 days, the strawberries coated with CFL-2 coatings film showed no signs of mildew and had a better appearance compared to the blank control group and the other groups with different coatings . The limited preservation effect of CFL-0 and CFL-1 coatings might be attributed to the insufficient concentration of d -Limonene, which have rendered them inability to effectively eliminate microorganisms present on the surface of the fruits . The freshness of strawberries soaked in the CFL-3 and CFL-4 coatings decreased as the concentration of d -Limonene increased.…”
Section: Resultsmentioning
confidence: 99%
“…After being coated by dipping and stored at a temperature of 19–25 °C and humidity of 40–50% for 7 days, the strawberries coated with CFL-2 coatings film showed no signs of mildew and had a better appearance compared to the blank control group and the other groups with different coatings . The limited preservation effect of CFL-0 and CFL-1 coatings might be attributed to the insufficient concentration of d -Limonene, which have rendered them inability to effectively eliminate microorganisms present on the surface of the fruits . The freshness of strawberries soaked in the CFL-3 and CFL-4 coatings decreased as the concentration of d -Limonene increased.…”
Section: Resultsmentioning
confidence: 99%
“…CS-coated phytochemical-encapsulated NPs might have increased antimicrobial activity. Our recent study indicated that CS-coated trans -resveratrol-encapsulated NPs inhibited the growth of S. enteritidis , L. monocytogenes , E. coli , and S. aureus as compared to trans -resveratrol-encapsulated NPs without CS, and further prolonged the shelf-life of strawberries after dipping into the NP solutions [ 54 ]. One aforementioned research implied that the presence of amino groups in CS could potentially facilitate the binding of lemongrass NP solution to the negatively charged bacterial surface, hence justifying its antimicrobial effects [ 46 ].…”
Section: Stabilizers For Phytochemical-based Nps Preparation and Thei...mentioning
confidence: 99%
“…Ultimately, freestanding films were fabricated by solution casting on the strawberry surface. The composite films revealed excellent antimicrobial activity, reduced dehydration and texture deterioration of fruit, and increased the absorption of resveratrol by oral administration [ 161 ].…”
Section: Applicationsmentioning
confidence: 99%